(untitled) (Scientific journal of the Fergana State University, 2023)
In article describes properties of irrigated soils of the Sukh river cone, ecosystem-reclamation state and classification of soils, agrochemical properties of soils developing on the territory. The mechanical composition of soils, genetic basis and systematic condition of soils are shown.